Non-standard employment in post-industrial labour markets: an occupational perspective (Cheltenham, 2015)
"Examining the occupational variation within non-standard employment, this book combines case studies and comparative writing to illustrate how and why alternative occupational employment patterns are formed. Non-standard employment has grown significantly in most developed economies, varying between countries. Different institutional settings have been deemed accountable for this variation, though inadequate consideration has been given to differences within national labour markets. Through an occupational perspective, this book contends that patterns of non-standard employment are shaped by flexibility in hiring and firing practices and the dispensability of workers' skills. The framework integrates explanations based on labour market regulation, industrial relations and skill supply, filling the gaps in previous scholastic research. A necessary and discernible insight into employment patterns, academics in the fields of economics and sociology will find this book of great value. Policy makers and practitioners alike will benefit from the comparative analysis of rich empirical material."